A Study on Clinical and Bacteriological Profile of Urinary Tract Infections (UTI) in North Karnataka - Chandrakala Guruprasad; Manjunath B M; Mohammed Abdul Quddus (RGUHS Journal of Medical Sciences)
Background The infection of urinary tract UTI is quite common with higher incidence in diabetics compared to non-diabetics. Women are most commonly affected compared to men with an incidence rate of 40 to 50. In recent years the etiology and antibiotic resistance of uropathogens have been evolving worldwide.Aim To investigate the impact of uropathogens and evaluate their drug susceptibility patterns in both diabetic and non-diabetic individuals.Methods This was a prospective study which included 100 patients. Mid-stream urine was collected in a sterile dry wide necked and leak proof container and tested using urine-analyzer. Urine culture was done using Kirby Bauer disc diffusion method and sensitivity was done using Mueller Hinton agar using different antibiotics.Results Out of 100 patients 54 were diabetics and 46 were non-diabetics. Most common age group affected was 60-70 years with females being more commonly affected. About 74 patients were symptomatic and 26 were asymptomatic. Fever was the most common symptom 41 followed by burning micturition 39. Cystitis was noted in 15 diabetic patients and 10 non-diabetic patients. About 22 of diabetic patients had Klebsiella pneumoniae infection 16 had Escherichia coli infection while 16 non-diabetics had K pneumoniae infection and 14 had E. coli infection. Both organisms were sensitive to Cephalosporins followed by Carbapenem group of drugs.Conclusion Maintaining good blood sugar control and proper hygiene plays a significant role in controlling infection of urinary tract. Complications of chronic UTI can be prevented by prompt treatment with appropriate antibiotics.